PENGARUH FAKTOR-FAKTOR CITY BRANDING BANDUNG SMART CITY TERHADAP PERSONAL BRANDING RIDWAN KAMIL SEBAGAI WALIKOTA BANDUNG - Koswara, Annisa Nur Muslimah (Kementerian Komunikasi dan Informatika R.I., 2020)
This study discusses the concept of city branding and personal branding. City branding typology which has been analysed is smart city. Then the personal branding which has been investigated is the leader of city. This research analyses the influence both of two concepts through quantitative research approach with explanative design. Respondents were 400 citizen in Coblong, Cicendo, Bandung Wetan, and Sumur Bandung District, which selected by quota sampling techniques. Techniques of data analysis, such as descriptive data analysis and linier regression to verify research hypotheses. While factors analysis is used to find the factors which influencing conformation Ridwan Kamil’s personal branding as the Mayor of Bandung city. The results showed a positive and significant influence of The City Branding’s Factors of Bandung Smart City towards Ridwan Kamil’s Personal Branding. On the other hands, this research show 2 (two) factors in city branding Bandung smart city conformation, such as place brand assets and values.